Quadratic planar systems with two parallel invariant straight lines - Buzzi, Claudio A. [UNESP]; Tonon, Durval J. (Springer Nature, 2009)
In this paper, we classify the global phase portraits of all quadratic planar systems with two parallel invariant straight lines. The main techniques used are Poincaŕe Compactification and Normal Forms Theory combined with the Neumann's Theorem. © 2008 Birkhäuser Verlag Basel/Switzerland.
Keywords: Phase portraits; Planar vector fields; Quadratic vector fields